PENGARUH PERUBAHAN SOSIAL TERHADAP LAHAN TIDUR DI DESA TOMBASIAN ATAS KECAMATAN KAWANGKOAN BARAT - Jennifer Umboh; Charles R. Ngangi; Rine Kaunang; Yolanda P.I. Rori (Universitas Sam Ratulangi, 2014)
ABSTRACTThe objective of this research is to determine the effect of social change especially attitudes and social values, for the increasing Idle land in the village of Tombasian Atas Kawangkoan West Subdistrict.Data collection was conducted for three months, since January 2014 until March 2014. Data obtained are primary and secondary data. The primary data obtained through the survey directly to the owners of idle land in the